HUBUNGAN FREKUENSI DAN DURASI MENYUSUI DENGAN KENAIKAN BERAT BADAN BAYI BARU LAHIR - Devya Nada; Mariyana (Universitas Batam, 2026)
Human Papillomavirus (HPV) infection often presents without symptoms and may go undetected. Cervical cancer is commonly found among women of reproductive age, typically between 15 and 45 years. Several factors can increase the risk of cervical cancer, including early sexual activity (before the age of 20), multiple sexual partners, early-age pregnancy, smoking, a history of sexually transmitted infections (STIs), high parity, use of hormonal contraceptives, consumption of immunosuppressive drugs, as well as unhealthy lifestyle and dietary habits. This study aimed to determine the relationship between the level of knowledge about cervical cancer and the attitudes toward HPV vaccination among women of reproductive age at Nagoya Clinic, Batam, in 2025. A cross-sectional study design was employed, with data analyzed using the chi-square test. The sample consisted of 55 women aged 15–49 years who visited or sought treatment at Nagoya Clinic, Batam City. The study found a statistically significant relationship between knowledge of cervical cancer and attitudes toward HPV vaccination among women of reproductive age (p-value = 0.009). Knowledge about cervical cancer is significantly associated with positive attitudes toward HPV vaccination. Increasing awareness and education regarding cervical cancer and HPV vaccination may contribute to improved preventive behaviors among women of reproductive age. Keywords : Human Papillomavirus, cervical cancer, reproductive age